2014
DOI: 10.2340/16501977-1852
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient-healthcare provider discussions on enrollment in cardiovascular rehabilitation

Abstract: While caution is warranted due to the number of comparisons undertaken such that associations observed may be chance associations, these novel findings suggest that not overstating the beneficial effects of acute treatment, and allowing patients more time to ask questions about needed lifestyle changes should be investigated in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Harms or adverse effects of interventions to increase CR utilization were not considered. An observational study has suggested that offering too much reassurance and optimism to patients about their recovery during CR discussions at the bedside may be associated with less enrolment [67]. While none of the interventions tested in the included studies were associated with significantly lower utilization, clearly the content of structured communications during interventions should be considered, standardized, and tested.…”
Section: Discussionmentioning
confidence: 99%
“…Harms or adverse effects of interventions to increase CR utilization were not considered. An observational study has suggested that offering too much reassurance and optimism to patients about their recovery during CR discussions at the bedside may be associated with less enrolment [67]. While none of the interventions tested in the included studies were associated with significantly lower utilization, clearly the content of structured communications during interventions should be considered, standardized, and tested.…”
Section: Discussionmentioning
confidence: 99%
“…First, literature regarding patient-provider discussions about CR was reviewed, including barriers [28,29]. Experts on patient-provider discussions regarding CR were consulted.…”
Section: Needs Assessmentmentioning
confidence: 99%
“…Some authors have commented that improving referral rates to CR does not mean that enrollment or participation rates will also improve (43,44). The gap between referral rate and the following enrollment rate could be explained by a number of factors (45,46), such as if healthcare providers expressed less optimism and reassurance during discussions about CR (47). Nevertheless, intervening at the level of referral is still key for improving enrollment rates (48).…”
Section: Potential Interventions and Future Directionsmentioning
confidence: 99%